(NhIMI^ESKOE IZU^ENIE DITERPENOWYH ALKALOIDOW TREH WIDOW RASTENIJ RODA (BACONITUM.-s (NdISSERTACIQ(B. 020010s - (NbATBAQR n(B.s; (NmONGOL uLSYN iH sURGUULXs ((Nub(B.s, 1996)
(NdISs
(NdIS(B-50s
Keywords: (NHIMIQs; (NBIOORGANI^ESKAQ HIMIQs; (NHIMIQ PRIRODNYH WE]EJWs; (NALKALOIDYs; (NDISSERTACIQs